Trabalho, saberes e a terra: as mulheres no assentamento Serra Dourada/GO - SOUZA, Jéssica Lorrane Gonçalves (Universidade Federal do Pará, 2022)
This research analyzed the work process for women in the Serra Dourada/GO Settlement, based on their actions in the context of planting vegetables. Thus, it reflected on the role that women play in their daily activities, that is, ahead of production, harvesting and planting activities, as well as whether the tasks performed by them interfere or not in the family economy. Through Oral History, it was possible to understand the stories of settled women who work with vegetable plantations and enabled us to reconstruct practices, impasses, conflicts experienced in the settlement and in the city. In this sense, the analyses will be centered on the life stories of women who somehow work within the community. We saw that some of these women are not recognized by the local society, but they mention that they recognize themselves in this process, as well as by the family.